PROFESIONAL HUKUM DENGAN MALPRAKTIK YANG DILAKUKANNYA SEBAGAI BENTUK PELANGGARAN DARI KODE ETIK PROFESI HUKUM - Hasanah, Uswatun (Universitas Prof. Dr. Hazairin, SH, 2021)
Legal professionals consisting of a judge, the prosecutor , advocate , notary and police in their profession sometimes doing malpractice whether intentional or tentional . Malpractice is a violation of the code of conduct that they have. So that legal professionals can be a qualified legal professionals is mandatory for them to follow the rules that bind them so that they can become legal professionals who are responsible for themselves , society and God Almighty. This research is a type of normative legal research, by examining laws and regulations, books, journals. In this study, the problem raised is how is malpractice among legal professionals as a form of violation of the code of ethics of the legal profession.